Evaluation of the level of e-learning in the extension institution in Iraq (Journal of the College of Basic Education, 2023)
The research aims to identify the level of e-learning in the extension institution in Iraq, by defining two areas for assessing the level of e-learning (learning, communication) and determining the relationship between the level of e-learning and some factors related to it.The research community included students of the fourth stage, Department of Agricultural Extension / College of Agriculture, Baghdad, and all agricultural extension workers working in the Directorate of Agriculture of Baghdad and its affiliated agricultural divisions, by 32 and 174, respectively. For the categories of students and agricultural extension agents 27 and 139, respectively.The questionnaire was used as a means to obtain the necessary data from the respondents, and the results of the statistical analysis showed that the general nature of the level of e-learning is average, and that there is a negative significant relationship with a probability level (0.01) between the level of e-learning and each of age and profession, and there is a negative significant relationship with a probability level (0.05). ) between the level of e-learning and gender.Based on the results of the research, we recommend the need for the General Authority for Agricultural Extension and Cooperation to involve agricultural extension agents in the Baghdad governorate periodically in training courses for e-learning, while giving greater importance to the two fields of research (learning, communication), for the purpose of improving the level of their extension performance, with the importance of intensifying the educational curricula for students of the department Agricultural extension topics of e-learning.